2018
DOI: 10.1111/jopr.12746
|View full text |Cite
|
Sign up to set email alerts
|

Rosemary, Castor Oils, and Propolis Extract: Activity Against Candida Albicans and Alterations on Properties of Dental Acrylic Resins

Abstract: Eight percent rosemary oil has the potential to be used as an acrylic resin disinfectant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
3
0
1
Order By: Relevance
“…These results agreed with those of Abed (2022), who found a nonsignificant difference in acrylic roughness after immersion in electrolyzed water (37) . Heidrich et al (2018) obtained the same results, that was, rosemary and castor oils and propolis extract had no damaging effect on the surface roughness of pink acrylic resin until the fourth month (38) . Similarly, Salman and Saleem (2011) demonstrated that when the heat acrylic resin was immersed in different denture cleaner solutions, the resin's surface was not affected (39) .…”
Section: Discussionmentioning
confidence: 65%
“…These results agreed with those of Abed (2022), who found a nonsignificant difference in acrylic roughness after immersion in electrolyzed water (37) . Heidrich et al (2018) obtained the same results, that was, rosemary and castor oils and propolis extract had no damaging effect on the surface roughness of pink acrylic resin until the fourth month (38) . Similarly, Salman and Saleem (2011) demonstrated that when the heat acrylic resin was immersed in different denture cleaner solutions, the resin's surface was not affected (39) .…”
Section: Discussionmentioning
confidence: 65%
“…Apesar do HS1% ser uma solução química com propriedade branqueadora, neste estudo, ele não foi capaz de alterar a coloração da resina acrílica. Estudo anterior (Heidrich et al, 2018) encontraram alteração de cor em todos os grupos de seu estudo quando espécimes de resina acrílica eram imersos em outros extratos (óleo de rícino, óleo de alecrim, extrato glicólico de própolis), bem como em água destilada e hipoclorito de sódio, porém por maior período de tempo que neste trabalho. Nossos diferentes achados podem se relacionar com o menor tempo de imersão utilizado e o fenômeno de sorção de água que a resina acrílica apresenta quando imersa em água por longos períodos (Fernandes et al, 2011).…”
Section: Discussionunclassified
“…In this sense, biopolymers of plant origin have been used for developing products to the biomedical field, including polyurethane [3][4][5][6][7][8] . Polyurethane from castor oil is a compound that consists of a prepolymer and a polyol extracted from the seed oil of the Ricinus communis plant, which does not exude toxic vapors and is a biocompatible material [9,10] .…”
Section: Introductionmentioning
confidence: 99%